Fit-risk in development projects: role of demonstration in technology adoption. (15th August 2016) - Parks, Moon; Bansal, Sangeeta; Zilberman, David
Abstract: The introduction and adoption of new technologies is an important component of development projects. Many technologies that could spur considerable increase in welfare, however, are often adopted at low rates even when donors and NGOs have invested their effort in them heavily. This paper develops a framework to analyze inefficiencies caused by fit-risk (potential users are not certain whether the technology will fit their needs, lifestyles, social feedback or capabilities), and the role of marketing tools, such as demonstration, in reducing fit-risk and enhancing the efficiency of development projects. We find that, in the presence of fit-risk, there is always unrealized demand and resource waste. Donors who ignore fit-risk always overestimate the project value and over-subsidize the products they are promoting. We identify conditions under which introducing demonstration may help alleviate fit-risk and improve the overall project values. The impact of eliminating fit-risk on the project uptake depends on the probability of fit.